Effect of Habituation to Milking and Natural Suckling on Milking Behaviour and Milk Production Characteristics in Primiparous Sahiwal Cows - Bharti, Pranay; Kamboj, Madan Lal (Indian Journal of Dairy Science, 2019)
The present study was performed to investigate the influence of habituation to milking and natural suckling on milking behaviour and milk production characteristics in primiparous Sahiwal cows. For this experiment 18 late pregnant Sahiwal heifers were selected and divided into 3 groups viz. non-habituated to milking routine and weaned, control (C), habituated to milking routine and weaned (T1) and habituated to milking routine and suckled (T2) group. The mean let-down time (C: 91.48, T1: 82.37, T2: 59.85 sec), milking temperament score (C: 2.11, T1: 1.83, T2: 1.33) and frequency of defecation (C: 0.85, T1: 0.81, T2: 0.62) were significantly (P